A Brief Study on Nonperforming Assets of Banks in India - R. S. N. Sharma (Modern Perspectives in Economics, Business and Management Vol. 6, 2021)
Accepting deposits and lending loans is the primary function of banks. They lend loans on certain terms and conditions. Some of the granted loans may be continuously, periodically and systematically repaid by the borrowers as per the agreed terms and conditions but may not be repaid in time and there may be time lag in repayment. Sometimes the time lag may become longer and irrecoverable. The loan granted by the bank is asset to the bank as it is receivable amount to bank. If the loan is being systematically repaid by the borrower, it is performing asset, otherwise if it is not being paid regularly and properly it is said to be non performing asset. If payments of interest and/ or principal are in default for more than 90 days period, generally it is considered as non-performing asset. Nonperforming assets are burden to banks. They adversely affect the performance of banks and sometimes increasing non-performing assets may lead to closure of business also. These should be regularly reviewed, monitored, analysed and ultimately controlled for the smooth running of bank. For this, a systematic regulatory mechanism must be employed and its perfect execution is to be ensured. (Newly Added: People without having an idea on this, if they deposit their hard earned money in banks with higher NPAs may have to lose their deposits even if Deposit insurance is there. Because deposit insurance is provided to certain extent only. Up to 5,00,000 only deposit insurance available.) In this paper an attempt has been made to make study on Non-Performing assets of banks in various sectors in India by using percentages, Indexed values. The study is completely based on secondary data collected from handbook of statistics of Reserve Bank of India. The collected data is tabulated, analysed and conclusions are drawn.